Paralympic health: emerging trends and innovations - Winckler, C.; Neto, F. R.; Gomes Costa, R. R.; Loturco, I.; Trigo, E. L.; Miranda, A. J.; Santos, L. G. (Frontiers in Sports and Active Living, 2026)
This article synthesizes recent developments in Paralympic Health, covering not only the conceptual evolution that supports athletes with disabilities in Paralympic sports but also the impact of scientific advances on health care and on the classification system, training, and competition. The Paralympic Games are not only a competitive event but also a driving force behind the development of assistive technology and the generation of knowledge about physical exercise for individuals with disabilities. Sports classification, based on increasing scientific evidence, is being consolidated by applying the impairment concept to three major groups: physical, vision, and intellectual. The most significant development in recent editions of the Games is epidemiological monitoring, which has made it possible to reduce the incidence of health problems. The interdisciplinary development of health based on science is fundamental in guaranteeing opportunity and equity for people with disabilities in Paralympic sports.